Absence of Epstein-Barr virus in oesophageal squamous cell carcinoma. Issue 4 (August 1995) - Lam, K Y; Srivastava, G; Leung, M L; Ma, L
Abstract : Aim —To identify the possible role of Epstein-Barr virus (EBV), in Chinese patients, in the pathogenesis of oesophageal squamous cell carcinoma. Methods —Formalin fixed, paraffin wax embedded tissues from 74 cases of oesophageal squamous cell carcinoma (28 with well differentiated, 27 with moderately differentiated and 18 with poorly differentiated carcinomas) were analysed for EBV using in situ hybridisation for EBV encoded small RNAs. Results —EBV was detected in only a few lymphocytes adjacent to the tumour epithelia in 14 (19%) cases of oesophageal carcinoma. The adjacent, non-pathological oesophageal tissue was EBV negative. Conclusions —EBV does not play a major role in the aetiology of oesophageal squamous cell carcinoma.